(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The modern technology to finance investments, of leasing, and the wide attention in the industrialized countries due to their particular flexibility, as well as their low costs often thus making them an alternative to compete with other traditional financing methods. It is noted in this regard that developing countries, especially Arab ones for the most part what relatively late still in the application of this type of financing , companies are leasing is still very low compared with the industrialized countries due to traditional methods control of funding for financial institutions, and non-acceptance risk in new areas of funding, lack of professionalism in the financial and banking field and then dodging relatively active participation in economic development; this study examine the decision to leasing the Iraqi environment as a source of funding for projects to identify extent the desire of the Iraqi projects and their ability to exercise Activity leasing, as well as the desire of the Iraqi banks and their ability to finance the leasing projects, According hypotheses of the study using a model according to the measure " Likert " questionnaire, the first model to the Iraqi projects, as leasing , and was (50) projects , in the face of the second model to the branches of Iraqi banks, as leased, the (40) bank. The study concluded the following results: The desire of the Iraqi projects, and their ability to exercise Activity leasing, as well as a statistically significant relationship between the knowledge of the project of leasing activity and flexible lease process, and pledges to the tenant project against for financing its assets on the one hand, and between the desire of the projects, and their ability to exercise leasing activity on the other.